The Free Nutritional Meal Program (MBG) in Supporting the Development of Elementary School Students: A Literature Study - Fauziah Wulansari; Nurul Mutmainah; Nisriina Amiirah Faatin; Murfiah Dewi Wulandari; Darsinah Darsinah (FKIP - Universitas Riau, 2026)
Optimal nutritional fulfillment is a crucial factor in supporting the development of elementary school students, both in terms of health and learning readiness. One national policy designed to address this issue is the Free Nutritional Meal Program (MBG). This study aims to analyze the role of the Free Nutritional Meal Program (MBG) in supporting the development of elementary school students and identify key findings and implementation challenges based on a literature review. This study used a qualitative approach with a literature review method on 20 relevant scientific articles published in the last five years and obtained through the Google Scholar, Garuda, and SINTA databases. The study results indicate that the MBG Program contributes positively to fulfilling students' nutritional needs, improving concentration and learning readiness, cognitive development, learning motivation, and character building and healthy lifestyle habits. However, the implementation of the MBG Program still faces various challenges, particularly related to the readiness of facilities and infrastructure, human resources, and program sustainability. Therefore, strengthening cross-sectoral coordination and a continuous monitoring system is needed so that the benefits of the MBG Program can be optimized in supporting the quality of basic education.